Acumulación de metales pesados en suelos agrícolas con cultivo de banano en el sector El Moral, recinto Santacruz, cantón La Maná, Provincia de Cotopaxi. - Medina Ruiz, Génesis Katherine (2017)
This research project entitled "Accumulation of heavy metals in agricultural land with banana cultivation in El Moral, Recinto Santacruz, Cantón La Maná, Cotopaxi Province", carried out from November 2016 to January 2017, Which deals with soil contamination by heavy metals from the use of fertilizers and pesticides containing chlorine, phosphates and carbamates, at the Ignolia Farm. The main objective is to estimate the accumulation of heavy metals in agricultural soils with banana crops. To determine the level of contamination, a sampling was performed which had 7 reference points at two depths, the first of 0-20cm and the second of 20-40cm. Physical analyzes (texture, MO, CE and humidity) were carried out at the Laboratory of Water and Soils of the UTEQ and the chemicals (cadmium, chromium and lead) at the Accredited Laboratory "Grupo Químico Marcos SA", at Exception of the pH which was analyzed in the Laboratory of the UTEQ. The owner of the hacienda and the administrator were interviewed and visited the hacienda, identifying the management of the plantation, consecutive visits were also carried out on the days when the banana was cut, obtaining information on the steps taken for the execution of Production, and also to obtain information on the types of fertilizers and pesticides used, the frequency of administration and the doses used per hectare. To determine if there were significant differences in cadmium, chromium and lead levels, statistical methods such as variance analysis (ADEVA) were applied, resulting in elevated cadmium levels and to determine if there was influence on any of the physical and chemical parameters on The accumulation of cadmium in the soil was applied the Pearson correlation coefficient determined that the pH is the only one that interacts with heavy metals. Based on the results obtained, it is proposed to implement the bioremediation plan for cadmium-contaminated soils, since this is the heavy metal that exceeds the maximum permissible limits established in Ministerial Agreement 097, Annex II, Table 1.